(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
The article is dedicated to a promising direction in concrete technology - the use of binary and multicomponent aggregate systems. A scientific hypothesis about the targeted control of the microstructure by combining fillers with different surface activity has been substantiated. The principle of dense packing of particles is considered.